Lama Sakit Diabetes Berhubungan dengan Fungsi Kognitif pada Pasien Diabetes Mellitus - Ika Nur Fitriani; Okti Sri Purwanti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the relationship between the duration of diabetes and cognitive function in patients with diabetes mellitus. The research method used is quantitative research with a cross-sectional design. The results showed that two respondents had diabetes mellitus <1 year and average cognitive experience, while four experienced cognitive impairment. Then those with diabetesâ‰¥ 1 year who experienced usual mental were three respondents, while those who experienced cognitive impairment were 58. Based on the results of the Spearman rho correlation test, it was found that the p-value was 0.028 <0.05. In conclusion, there is a relationship between diabetes mellitus duration and cognitive function in diabetes mellitus patients, with a weak correlation. Keywords: Diabetes mellitus, Cognitive function, Length of diabetes